Pulmonary Protein Oxidation and Oxidative Stress Modulation by Lemna minor L. in Progressive Bleomycin-Induced Idiopathic Pulmonary Fibrosis - Yanka Karamalakova; Ivaylo Stefanov; Ekaterina Georgieva; Galina Nikolova (MDPI AG, 2022)
Bleomycin (BLM) administration is associated with multifunctional proteins inflammations and induction of idiopathic pulmonary fibrosis (IPF). Lemna minor L. extract, a free-floating monocot macrophyte possesses antioxidant and anti-inflammatory potential. The aim of the study was to examine the protective effect of L. minor extract on lung protein oxidation and oxidative stress modulation by BLM-induced pulmonary fibrosis in Balb/c mice. For this purpose, the protein carbonyl content, advanced glycation end product, nitroxide protein oxidation (5-MSL), and lipid peroxidation (as MDA and ROS), in lung cells were examined. The histological examinations, collagen deposition, and quantitative measurements of IL-1β, IL-6, and TNF in lung tissues and blood were investigated. Intraperitoneal, BLM administration (0.069 U/mL; 0.29 U/kg b.w.) for 33 days, caused IPF induction in Balb/c mice. Pulmonary combining therapy was administered with L. minor at dose 120 mg/mL (0.187 mg/kg b.w.). L. minor histologically ameliorated BLM induced IPF in lung tissues. L. minor significantly modulated (p < 0.05) BLM-alterations induced in lung hydroxyproline, carbonylated proteins, 5-MSL-protein oxidation. Oxidative stress decreased levels in antioxidant enzymatic and non-enzymatic systems in the lung were significantly regulated (p < 0.05) by L. minor. L. minor decreased the IL-1β, IL-6, and TNF-α expression in lung tissues and plasma. The L. minor improves the preventive effect/defense response in specific pulmonary protein oxidation, lipid peroxidation, ROS identifications, and cytokine modulation by BLM-induced chronic inflammations, and could be a good antioxidant, anti-inflammatory, and anti-fibrotic alternative or IPF prevention involved in their pathogenesis.